PENGARUH METODE LATIHAN PLYOMETRICS DAN KEKUATAN OTOT TUNGKAI TERHADAP PENINGKATAN KETEPATAN TEMBAKAN SEPAKBOLA - TEDDY AGOENG SOELISTYO (Jurnal Ilmiah Spirit, 2012)
This research aims to find out: (1) the difference between the effect of plyometrics knee tuck jump training and plyometrics squat jump training on increased football kicking accuracy, (2) the difference of increased football kicking accuracy between students with high and low leg muscle strength, (3) the interaction effect between the plyometrics training method and leg muscle strength on increased football kicking accuracy. Â  This research employed an experimental method with 2 x 2 factorial design. The population of the research in the students achievement coaching football of Teaching and Learning Faculty of Surakarta Tunas Pembangunan University, as many as 60 students. The sampling technique was purposive random sampling. ANOVA was used to analyzing data, the data analysis prerequisite test was done using the sample normality test (Lilliefors test with Î± = 0.05%) and variance homogeneity test (Bartlett test with Î± = 0.05%). Â  Based on the result of the analysis, conclusions are drawn as follows: (1) There is a difference plyometrics knee tuck jump training and plyometrics squat jump training on increased football kicking accuracy. The effect of plyometrics squat jump training is better than that plyometrics knee tuck jump training, (2) there is a difference on increased football kicking accuracy between the students with high and low leg muscle strength. The effect to on increased football kicking accuracy between the students with high leg muscle strength is better then the one with low leg muscle strength, (3) there is a effect of interaction between plyometrics training method with leg muscle strength on increased football kicking accuracy. The students with high leg muscle strength has according if it is plyometrics knee tuck jump training. While the students with low leg muscle strength has according if it is plyometrics squat jump training. Â